Perwatakan Tokoh Pergerakan Feminisme dalam Novel Ahlâm Al-Nisâ Al-Harem Karya Fatima Mernissi (Sebuah Kajian Strukturalisme Genetik) - Syarifuddin Syarifuddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This article describes the figures of feminist movements in the novel Ahlâm Al-Nisâ Al-Harem by Fatima Mernissi, a Moroccan sociologist and writer, who has contributed and influenced the development of modern Arabic literature. Using Goldmann's genetic structuralism approach, the author is interested in researching this novel because it pictures women leaders who aggressively carried out feminist movements in order to break down the boundaries of custom that narrow women's movements. This research uses qualitative data in the form of facts, information, statements or images obtained from the primary source: Ahlâm Al-Nisâ Al-Harem by Fatima Mernissi. The data were analyzed using a descriptive qualitative method focusing on content analysis, which is an in-depth analysis of the content of written information.